Lead Uptake in Acidic Medium by Lemna minor - Kaur, Leela; Gadgil, Kasturi; Sharma, Satyawati (Asian Journal of Chemistry, 2010)
The present paper discussed the assimilation of lead by Lemna minor in acidic (acetic acid and nitric acid) medium (pH ranging from 4-6).